Enhancing Student Learning Outcome in Social Studies: An ePub-Based Approach to Creative Economy Topics - Marwan Marwan; Ayang Marsnely; Tri Kurniawati (Economics Education Department Universitas Negeri Semarang, 2025)
This study aims to: develop EPUB-based teaching materials for social studies subjects, assess the feasibility of EPUB-based teaching materials for social sciences and creative economy topics, and evaluate the improvement in student learning outcomes after using the EPUB materials. The research employs a research and development (R&D) methodology, comprising five phases: analysis, design, development, implementation, and evaluation. The quality of the developed media was validated through expert judgment, while its effectiveness was evaluated through classroom application. The research subjects were students from two junior high schools. The implementation phase involved experimental and control groups at each school. Data were collected through student questionnaires to assess the practicality and effectiveness of the EPUB-based teaching materials. The results indicated that the media received high-quality ratings in terms of content, design, and programming, as evaluated by experts. Furthermore, both students and teachers considered the media to be highly practical and well-suited to meet the needs of students. An independent sample t-test conducted showed statistically significant differences in learning outcomes. The results indicate that students who used the EPUB-based media outperformed those who did not. In conclusion, the EPUB-based teaching materials are of high quality, practical, and effective, making them suitable for classroom implementation to enhance student learning outcomes.